Is spending on proton beam therapy for cancer going too far, too fast?. (17th April 2012) - Epstein, Keith
Abstract : Both the US and UK are pouring money into proton accelerators, which have been described as the world's "most costly medical devices." Keith Epstein asks if the investment is premature